Building Farmer Loyalty Through Marketing Mix and Brand Image of Tomato Seeds: The Mediating Role of Satisfaction Using PLS-SEM Approach - Muhammad Khoirudin; Mimin Aminah; Irni Rahmayani Johan (Jurnal Penelitian Pendidikan IPA, 2026)
Seed manufacturers face market share erosion due to fragmented execution. While prior studies partially evaluate inputs, integrated 7Ps and brand image frameworks remain scarce. This study evaluates structural relationships and satisfaction’s mediating role in the hybrid vegetable seed sector. Data were gathered from 171 tomato smallholders across 14 sub-districts in Cianjur Regency via a purposive sampling technique and analyzed using PLS-SEM. The model revealed that farmer satisfaction was strongly explained (R2 = 0.599), where brand image had the most dominant direct effect (β= 0.60, p < 0.00), followed by the marketing mix (β= 0.330, p< 0.00). Conversely, loyalty registered low variance (R2 = 0.15). Bootstrapping confirmed that satisfaction directly drove loyalty (β= 0.24, p=0.00). The core novelty lies in integrating high-dimensional 7Ps with an empirical screening filter for multi-brand retention. Mechanistically, satisfaction fully mediates the marketing mix (βindirect= 0.08, p= 0.01) and partially mediates brand image (βindirect)=0.15, p=0.00). Managerially, firms must shift from mass-branding to localized high-touch agronomic support to secure loyalty.